Economic analysis and randomised controlled trials: an investment appraisal approach - Backhouse, Martin E. (2006)
Randomised controlled trials (RCTs) play a fundamental role in the development and marketing activities of pharmaceutical companies. They are the primary means of evaluating the tolerability, safety and efficacy of a drug, and for providing information relevant for pricing and reimbursement decisions and clinical decision-making. RCTs require a substantial investment by pharmaceutical companies and the financial consequences of poorly or sub-optimally designed trials are potentially substantial. Revenue does not materialise unless a licence to market a product is granted and sales may be restricted if a trial fails to provide evidence of sufficient strength or relevance for those involved in product adoption decisions. From a pharmaceutical company's perspective, the value of RCTs can therefore be judged on the contribution they make to the performance of a drug in the market and hence on their contribution to the performance of the firm. Consequently the design choices made in the planning of RCTs are effectively investment appraisal decisions. However, the application of investment appraisal techniques to RCT design has not previously been proposed.